Comparison of endoscopic and endoscope-assisted microscopic transsphenoidal surgery for pituitary adenoma resection: a prospective randomized study - Eördögh, Márton; Bárány, László; Rosenstengel, Christian; Bogaczyk, Victoria; Baldauf, Jörg; Vogelgesang, Silke; Stahl, Andreas; Kirsch, Michael; Hosemann, Werner; Steveling, Antje; Al Menabbawy, Ahmed; Schroeder, Henry W. S. (Frontiers in Endocrinology, 2025)
ObjectiveThe value of endoscopic versus microsurgical approach has not yet been defined in transsphenoidal pituitary adenoma surgery. In this study, we compare both methods and analyze the long-term surgical, radiological, endocrinological, ophthalmological, and rhinological results as well as the patients’ quality of life.MethodsA total of 33 individuals with elective transsphenoidal pituitary adenoma surgery were randomized (pure endoscopic approach or endoscope-assisted microscopic approach) and prospectively underwent investigations with a focus on patient-related subjective outcome measurements.ResultsThe mean follow-up period was 6.3 years. In the microsurgical group, endoscopic inspection revealed residual tumor in seven of 15 patients (46.7%) not seen by the microscope. Endoscopic resection provided long-term tumor-free state in all of them. Compared to pure microsurgical treatment, endoscopy was associated with a lower probability of tumor recurrence (OR = 0.24) and appeared advantageous in the long-term achievement of any surgical goal (OR = 3.80) as well as in anterior pituitary lobe function improvement (OR = 1.60). Where gross total tumor resection was the stated preoperative goal, there was no long-term tumor recurrence in 81.8% (endoscopy group) and 83.3% (endoscope-assisted microsurgical group). Most aspects showed no significant difference between the techniques, such as length of hospital stay, complication rate (endoscopy: 16.7%, endoscope-assisted microsurgery: 20.0%), long-term maintenance of any preoperatively stated extent of resection, pituitary and olfactory function, rates of DI and SIADH, ophthalmological improvement, and SNOT scores.ConclusionsBoth techniques provide good long-term surgical, radiological, endocrinological, rhinological, and ophthalmological results. Endoscopy clearly improved the rate of long-term achievement of the initial surgical goal and the anterior pituitary lobe function.